Portuguese Manufacturing Industry in the sub-region of EDV: An Application of ELECTRE III - Sousa Lima, Antonieta Maria (2018)
The purpose of this study is to construct a ranking of industrial organizations that operate in the sub-region of EDV for ethical code. Thus, we use the methodology ELECTRE III as a tool to build a rank in the industries and differentiate it with financial ratios: return on equity, return on assets, financial autonomy and general liquidity. These four ratios allow to distinguish the organizations based on its performance compared with the market average. This information is provided by the Bank of Portugal. Using data from 2010 to 2013, only focusing on industrial organizations, because these characterize the structure of business in the sub-region. This study uses a descriptive analysis, which permits to conclude that, from the sample of 185 industries, after using the exclusion criteria, it was divided in nine sub-samples, resulting in most of the organizations to belong in one of the three first places in the ranking. We also conclude that, of these companies, there are high levels of exports, the majority being in line with the market’s average, here measured by the Statistics of the Bank of Portugal.